High Accuracy 14C Measurements for Atmospheric CO 2 Samples from the South Pole and Point Barrow, Alaska by Accelerator Mass Spectrometry - Meijer, H.A.J.; Pertuisot, M.H.; Van Der Plicht, J. (Environmental System Science Data Infrastructure for a Virtual Ecosystem, 2006)
Accelerator mass spectrometry (AMS) was used to obtain 14 CO 2 measurements from flasks collected at the South Pole and Point Barrow, Alaska, USA, at the Scripps Institute of Oceanography network station (Keeling et al., 1989) (see also http://cdiac.ess-dive.lbl.gov/trends/co2/sio-bar.html). Air samples for years 1985-1991, originally collected in 5-liter flasks, had been stored in Pyrex sealed-off tubes after stable isotope analysis (Roeloffzen et al., 1991). These samples were more or less evenly distributed over time.Typically, the extracted CO 2 from 2-5 flasks from consecutive weekly measurements were put together in one flame-off tube. The tubes were broken in the standard inlet arrangement of a dual inlet stable isotope ratio mass spectrometer,and a stable isotope measurement was performed using the same instrument used in the original analyses (Roeloffzen et al., 1991).Then, the CO 2 was cryogenically trapped and converted to graphite (Aerts-Bijma et al., 1997). For the majority of the samples the amount of CO 2 was sufficient for our regular, 2 mm diameter AMS targets, containing about 1.5 mg of C. For most of these, two targets could be produced from one CO 2 flask. In some cases, however, the amount of CO 2 was only sufficient for a smaller target.Individual standard samples were graphitized along with the corresponding atmospheric CO 2 samples, so that any day to day variability in the graphitization circumstances would be visible in the standard samples.The 14 C is reported as Δ 14 C as per Stuiver and Polach 1977. More information about 14 C standards can be found at: http://www.c14dating.com/agecalc.html.More information about sample preparation and analysis at the Groningen AMS can be found at: http://www.rug.nl/ees/onderzoek/programmas/radiocarbonams/sampleTreatmentAms The primary literature reference for the material presented here is Meijer et al. (2006).The statistical analysis included curve fitting described by Cleveland (1979). A seasonal pattern was then fit to the residuals, and the data are given in terms of these trends and departures from them.